Generating 3D building models according to Swedish building specification using footprints and airborne laser scanning - Klasson,Andreas (Master Thesis in Geographical Information Science, 2025)
Buildings are a central component of three-dimensional (3D) city models. Generating such models according to an appropriate standard is not always straightforward and can be time-consuming. This study explores a method for generating building models that comply with the Swedish national specification (NS) for buildings, at a level of detail (LOD) that includes roof structures. The method evaluates how building footprints from the national building register, combined with open airborne laser scanning (ALS) data with a point density of 3.7 points/m2, can be used to generate buildings with flat and gable roofs. A semi-automatic approach is used, applying the RANSAC algorithm to detect roof planes and calculate their intersections. The results show that the successfully generated buildings had a root mean square error (RMSE) in height of 0.15 m for gable roofs and 0.21 m for flat roofs, when compared to reference points. For gable roofs, the ridge endpoint location had a planar RMSE of 0.09 m. However, only simple roof shapes and structures could be accurately generated. Buildings with complex roof geometries or varying roof heights were not successfully modelled. The planar accuracy reflects the high quality of the building footprint data, while the height accuracy demonstrates the method’s suitability for simple gable and flat roofs on buildings that do not require further segmentation due to height differences. This study highlights a viable approach for generating accurate building models of simple structures that comply with the Swedish NS building standard.
Keywords: Geography; GIS; Arial Laser Scanning; ALS; Building model; Level of Detail; LOD; RANSAC; National Specification Building